Food and Environment in Early and Medieval China - E. N. ANDERSON (University of Pennsylvania Press, 2014)
This book covers the development of the Chinese food system from earliest times into the Ming Dynasty. Most attention is devoted to recent work on predynastic China and on the Yuan Dynasty, since these are both key to the system and the subjects of recent major research. Considerations of space have made me leave most of Ming and all of Qing and postimperial China for other venues, but I provide conclusions about Chinaâ€™s food system at the end of imperial times in the early twentieth century, as well as a few comparisons with recent times. For notes on later times, see my website postings â€œMing and Qing: Population and Agricultureâ€ on late imperial food and science, â€œChinaâ€™s Environmental Ruinâ€ on contemporary mainland China, and â€œChinese Food Updatesâ€ on contemporary food ethnography (www.krazykioti.com). These are works in progress, are not to be taken as final, and not to be cited without my permission. This book owes everything to Victor Mair, who expressed interest in my work and helped and encouraged at every stage. I also owe an enormous debt to my lifelong coworker Paul Buell, and to many friends and helpers in the world of Asian food, especially those who kept contact and remained encouraging during my long years away from China studiesâ€”including Jacqueline Newman, Charles Perry, FranÃ§oise Sabban, and others. Many more recent friends and fellow scholars have also helped with the enterprise, including Sidney Cheung, David Knechtges, Zelda Liang, Nick Menzies, Tan Chee-Beng, Jianhua â€œAyoeâ€ Wang, and Sumei Yi. Peter Agree has served ably as editor, and I am deeply grateful to Alison Anderson and Gail Schmitt for extremely detailed and careful copy-editing. Thanks also for incredible experiences in a lost world, to Choi Kwok-tai and Cecilia Choi, and to Chow Hung-fai; and to Purevsuren Tsolmonjav for an intense and inspiring introduction to Mongolian life and environment. Finally, I am deeply grateful, as always, to my wife Barbara and our children, children-in-law, and grandchildren; they give me life itself.